Impact of compensation package on job attrition: A study on teaching professionals - Hoque, Kazi Enamul; Mosa, F.Z.; Mishra, P.K.; Leng, C.H.; Darusalam, Ghazali (Marsland Press, 2013)
This study seeks to describe the impact of compensation package on employees’ job attrition. Data from a representative sample of North province secondary school teachers from Maldives (n = 206) were gathered through questionnaires. Multiple and Hierarchical multiple regression analysis were used in this research. This study found significant impacts of some of the components such as intrinsic compensation package on teachers’ attrition. Also found that teachers’ attrition can be minimized if schools put more emphasis on teachers’ intrinsic benefit such as instructional supervision and promotion. Though extrinsic benefits such as salary, merit pay, increment and overtime pay have impact on teachers’ attrition, it is not significant. This study will benefit the policy makers to find the ways of employees’ attrition especially in the countries where attrition is high as much as 11% in Maldives.